PHealth 2012 Proceedings of the 9th International Conference on Wearable Micro and Nano Technologies of Personalized Health June 26-28, 2012, Porto, Portugal - Blobel, Bernd (IOS Press, 2014)
The 2012 pHealth conference is the 9th in a series of scientific events bringing together expertise from medical, technology, gaming, and social care domains all related to the provision of personalized health services. Aspects such as health games, terminologies and ontologies as well as social and ethical aspects of health provision are to be addressed by more than 40 speakers from various parts of the world. Keynotes, invited talks, oral presentations and posters, addressing requirements and R&D outcomes enabling the paradigm change towards personalized health, together with demonstrations of existing and emerging applications in the pHealth domain will complement round table discussions and the ambition to define road-mapping activities focusing on the year 2020.